Determinants of institutional care willingness among Chinese older adults: an Andersen’s model-based analysis in Jiangning District, Nanjing - Zong, Ling; Chen, Zhengfang (Frontiers in Public Health, 2025)
IntroductionBy comprehensively examining the acceptance and preferences of older adults toward institutional care, and conducting an in-depth analysis of the various factors that influence these attitudes, we can gain a clearer understanding of their care needs. This insight will help deliver more appropriate and personalized care services and provide a scientific foundation for governments and social organizations to develop relevant policies and service programs.MethodsA sample of older adults from Jiangning District, Nanjing, was selected as the research subjects. The questionnaire was designed based on the Andersen’s Model, and a multi-stage mixed sampling method was adopted to investigate older adults’ willingness toward institutional care. Additionally, a binary logistic regression model was employed to analyze the factors influencing their willingness.ResultsA total of 415 valid survey data were collected, among which 44% of the surveyed older adults expressed willingness to choose institutional care. Correlation analysis revealed that there are key influencing factors within predisposing factors, enabling factors, and need factors, all of which exert an impact on the willingness toward institutional care. Further logistic regression analysis indicated that factors such as stigma associated with institutional care, participation in endowment insurance, purchase of medical insurance, perceived attitudes of children toward care institutions, accessibility of resources in care institutions, self-rated physical health status, and presence of chronic diseases may be influencing factors of the older adults’ willingness toward institutional care.ConclusionCompared with other regions in China, older adults in Jiangning currently have a relatively high willingness toward institutional care, which is influenced by multiple factors. Specifically, after incorporating predisposing factors, enabling factors, and need factors simultaneously into the model, older adults who held an open attitude toward institutional care, had endowment insurance and medical insurance, perceived their children’s positive attitudes toward care institutions, had easier access to institutional care resources, reported relatively good self-rated physical health, and had no chronic diseases demonstrated a stronger willingness toward institutional care.